Effect of temperature and pressure to pinning centers in bulk MgB2 under high pressure: Международная научно-практическая конференция «Нанотехнологии и наноматериалы» (Буковель, Украина, 29 августа–1 сентября, 2013 г.) - Kozyrev, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The MgB2-based samples were synthesized at 2 GPa at 800 and 1050 °C for 1 hour with and without Ti and SiC. X-ray, SEM and Auger structural studies showed that with increasing of manufacturing temperature grain boundary pinning transforms into point pinning, which is well correlated with the transformation of discontinuous oxygen enriched layers into separately located Mg–B–O inclusions in MgB2. Ti and SiC additions can influence the oxygen and boron distribution, but cannot change the type of pinning at relatively low temperatures.